Unconventional computation and natural computation : 15th International Conference, UCNC 2016, Manchester, UK, July 11-15, 2016, Proceedings /: 15th International Conference, UCNC 2016, Manchester, UK, July 11-15, 2016, Proceedings. (2016) - Unknown
No abstract available